When elephants were young [videorecording (DVD)] - Shatner, William (House Lights Media, 2017)
A young man and his young elephant, Nong Mai, begin in gritty Bangkok, Thailand, amid the controversial elephant business that threatens their very survival, until the opportunity comes to release Nong Mai to the wild.